Efficient optimization‐oriented design methodology of high‐order 3‐D filters using 2‐D and 3‐D electromagnetic simulators. (12th July 2014) - Hinojosa, J.; Quesada‐Pereira, F. D.; Bozzi, M.; Alvarez‐Melcon, A.
Summary This paper proposes a computationally highly efficient interface between two‐dimensional (2‐D) and three‐dimensional (3‐D) electromagnetic (EM) simulators for the optimization‐oriented design of high‐order 3‐D filters. In a first step, the novel optimization‐oriented design methodology aligns the 3‐D EM simulator response with the 2‐D EM simulator response of a low‐order 3‐D filter by using an inverse linear space mapping optimization technique. Then, a second mapping performs a calibration with the optimal 2‐D and 3‐D design parameters obtained from the first mapping. The optimization of high‐order filters is carried out using only the efficient 2‐D EM simulator, and the calibration equations directly give the design parameters of the 3‐D filter. The potential and the effectiveness of the proposed optimization‐oriented design methodology are demonstrated through the design of C‐band 3‐D evanescent rectangular waveguide bandpass filters with increasing orders from three to eight. Copyright © 2014 John Wiley & Sons, Ltd.